The associated factors for physical activity-related injuries among first-year university students in southern China from a biopsychosocial perspective - Xu, Lingyu; Chen, Shangmin; Gao, Dongna; Fang, Ying; Li, Liping (Frontiers in Public Health, 2024)
Background: Understanding the diverse factors influencing physical activity-related injuries is crucial for developing effective interventions that enable individuals to participate in physical activity (PA) while minimizing injury risk. Currently, research evidence on the multiple factors associated with PA-related injuries is inadequate. This study aimed to examine the associations between PA -related injuries and various biological, psychological, and social factors among first-year university students in China.We recruited first-year university students from Shantou University in Guangdong Province, China, to participate in our study. Data collection employed a structured self-administered questionnaire, gathering information on PA-related injuries, as well as relevant biological, psychological, and social factors. Binary logistic regression, using a stepwise modeling approach, was employed for the data analysis.Results: Among 1,051 first-year university students, 28.16% reported having experienced PA -related injuries in the past year. Most of the injuries reported were minor, with the knee or lower leg being the most frequently injured part of the body.Improper posture, environmental conditions, and excessive physical load were the leading causes of PA-related injuries. Multiple logistic regression analysis revealed that female students (OR=0.67, 95% CI: 0.47-0.94, p=0.022) had reduced odds of PArelated injuries. Conversely, high neuroticism (OR=1.61, 95% CI: 1.07-2.41, p=0.022), being a member of a sports team (OR=2.09, 95% CI: 1.34-3.27, p<0.001), PA on the wet ground (OR=1.73, 95% CI: 1.18-2.54, p=0.005) increased the odds of PA-related injuries.: Our findings underscore the intricate interplay of various factors contributing to PA-related injuries. Identifying high-risk individuals based on physiological and psychological characteristics, coupled with targeted interventions addressing modifiable risk factors, is crucial for effective prevention.